A novel surgeon credentialing and quality assurance process using transoral surgery for oropharyngeal cancer in ECOG-ACRIN Cancer Research Group Trial E3311. (November 2020) - Ferris, Robert L.; Flamand, Yael; Holsinger, F. Christopher; Weinstein, Gregory S.; Quon, Harry; Mehra, Ranee; Garcia, Joaquin J.; Hinni, Michael L.; Gross, Neil D.; Sturgis, Erich M.; Duvvuri, Umamaheswar; Méndez, Eduardo; et al.
Highlights: Transoral surgery is FDA approved for removal of oropharynx cancer. Credentialing and quality assurance can standardize surgical clinical trials. Our results may apply to other surgical disciplines and clinical trials. Abstract: Purpose: Understanding the role of transoral surgery in oropharyngeal cancer (OPC) requires prospective, randomized multi-institutional data. Meticulous evaluation of surgeon expertise and surgical quality assurance (QA) will be critical to the validity of such trials. We describe a novel surgeon credentialing and QA process developed to support the ECOG-ACRIN Cancer Research Group E3311 (E3311) and report outcomes related to QA. Patients and methods: E3311 was a phase II randomized clinical trial of transoral surgery followed by low- or standard-dose, risk-adjusted post-operative therapy with stage III-IVa (AJCC 7th edition) HPV-associated OPC. In order to be credentialed to accrue to this trial, surgeons were required to demonstrate active hospital credentials and technique-specific surgical expertise with ≥20 cases of transoral resection for OPC. In addition, 10 paired operative and surgical pathology reports from the preceding 24 months were reviewed by an expert panel. Ongoing QA required <10% rate of positive margins, low oropharyngeal bleeding rates, and accrual of at least one patient per 12 months. Otherwise surgeons were placed on hold and not permitted to accrue until re-credentialed using a new series of transoral resections. Results: 120 surgeons trained in transoral minimally invasive surgery applied for credentialing for E3311 and after peer-review, 87 (73%) were approved from 59 centers. During QA on E3311, positive final pathologic margins were reported in 19 (3.8%) patients. Grade III/IV and grade V oropharyngeal bleeding was reported in 29 (5.9%) and 1 (0.2%) of patients. Conclusions: We provide proof of concept that a comprehensive credentialing process can support multicenter transoral head and neck surgical oncology trials, with low incidence of positive margins and *grade III/V oropharyngeal bleeding.